Enhanced Placental Mitochondrial Respiration in Tibetan Women at High Altitude - Liu, Huifang; Tenzing, Noryung; van Patot, Martha Tissot; Qile, Muge; Ge, Ri-li; Wuren, Tana (Frontiers in Physiology, 2021)
Living at high altitudes is extremely challenging as it entails exposure to hypoxia, low temperatures, and high levels of UV radiation. However, the Tibetan population has adapted to such conditions on both a physiological and genetic level over 30,000 to 40,000 years. It has long been speculated that fetal growth restriction is caused by abnormal placental development. We previously demonstrated that placentas from high-altitude Tibetans were protected from oxidative stress induced by labor compared to those of European descent. However, little is known about how placental mitochondria change during high-altitude adaptation. In this study, we aimed to uncover the mechanism of such adaptation by studying the respiratory function of the placental mitochondria of high-altitude Tibetans, lower-altitude Tibetans, and lower-altitude Chinese Han. We discovered that mitochondrial respiration was greater in high-altitude than in lower-altitude Tibetans in terms of oxidative phosphorylation (OXPHOS) via complexes I and I+II, electron transfer system (ETS) maximum capacity, and non-phosphorylating respiration, whereas non-ETS respiration and OXPHOS via complex IV did not differ. Respiration in lower-altitude Tibetans and Han was similar for all tested respiratory states. Placentas from high-altitude Tibetan women were protected from acute ischemic/hypoxic insult induced by labor, and increased mitochondrial respiration may represent an acute response that induces mitochondrial adaptations.